Perinatal programming of appetite regulation and metabolic health - Dellschaft, Neele S. (2012)
According to the concept of perinatal programming environmental factors during fetal development and early postnatal life can influence phenotype in later life by modifying organ and tissue development and the epigenetic information of specific genes which, in turn, induce alteration in gene expression. Global nutrient restriction is a well-established intervention to study fetal programming but choline, a micronutrient essential for tissue growth and development, has not been extensively studied. The aim of this thesis is to investigate long term effects of modifications in maternal macro and micronutrient intake on the offsprings‟ appetite regulation and metabolic health. Twin-pregnant sheep were fed to requirements until 110 days of gestation and then randomised to stay on the same diet (R) or be restricted to 60% of caloric requirements (N) until term (~145 days). Offspring were subsequently subject either to a standard early postnatal growth rate as both twins remained with the mother (S) or to an accelerated growth rate resulting when only one twin remained to be mother fed (A). After weaning, offspring were reared in either a lean (L) or an obesogenic environment (O) until 17 months of age. These interventions gave rise to 4 groups: RAO, NAO, NSO and NSL. There were no differences in body weight, composition or adipocyte size with perinatal nutrient restriction but insulin response to a glucose tolerance test was increased in offspring born to N mothers. Measurement of hypothalamic gene expression in the latter offspring suggested a more orexigenic and cortisol-sensitive regulatory phenotype. During lactation, rats were fed a diet that was either choline-devoid (D), or contained a standard amount of choline either as bitartrate (C) or as phosphatidylcholine (PC). After weaning, female offspring were maintained on a standard choline diet until 11 weeks of age. D mothers had a substantial decrease in food intake and offspring were smaller at weaning but had similar glucose tolerance. Adult offsprings‟ brain phospholipid concentrations were reduced, which may suggest changes in brain development, but food intake and hypothalamic protein expression were unchanged. Intake of different forms of choline, i.e. bitartrate versus PC, during lactation had no long term effects on offspring. Both maternal dietary interventions had long term effects on offspring. Sheep developed the most adverse metabolic phenotype when the offspring were subjected to slow growth in late gestation followed by rapid growth and obesity, with the onset of insulin resistance mediated through changes in peripheral tissues. Maternal choline intake during lactation is essential for the health of the offspring as it alters brain composition. In conclusion, both studies produced results which are consistent with the concept of perinatal programming as adult metabolic health was affected in the sheep study and organ development was affected in a long term manner in the rat study.